1980
DOI: 10.1002/1097-0142(19800501)45:9<2383::aid-cncr2820450924>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme pathology of the liver in patients with and without nonhepatic cancer

Abstract: Preliminary studies of 13 enzymes subserving various metabolic pathways were undertaken in tumor-free liver biopsy samples from cancer patients and control subjects. The observations indicate that as a result of nonhepatic neoplasms, with (7 cases) or without (6 cases) hepatic involvement, the biochemical composition of the liver becomes partially undifferentiated. Quantification of appropriate enzymes in histologically normal liver samples could thus distinguish clearly between cancer hosts and controls. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

1982
1982
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…[21][22][23][24][25][26][27][28][29][30] However, in the latter types of liver disease, metabolic alterations can be explained by massive losses of normal cells and consequent regenerative responses within the liver, whereas no such visible signs accompany the pathophysiological changes in the cancer-free liver of patients with a distant malignant tumour. 8 The metabolic abnormalities observed here in cancer patients are therefore remarkable, supporting the view of cancer as a systemic rather than a local disease. Prospective studies will be needed in order to assess the etiological role of the observed abnormalities, as well as their prognostic value for subsequent weight loss and survival in human cancer.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…[21][22][23][24][25][26][27][28][29][30] However, in the latter types of liver disease, metabolic alterations can be explained by massive losses of normal cells and consequent regenerative responses within the liver, whereas no such visible signs accompany the pathophysiological changes in the cancer-free liver of patients with a distant malignant tumour. 8 The metabolic abnormalities observed here in cancer patients are therefore remarkable, supporting the view of cancer as a systemic rather than a local disease. Prospective studies will be needed in order to assess the etiological role of the observed abnormalities, as well as their prognostic value for subsequent weight loss and survival in human cancer.…”
Section: Discussionsupporting
confidence: 74%
“…7 Enzyme studies in tumour-free liver biopsies from patients with distant tumours and healthy control subjects revealed marked abnormalities in the liver of cancer hosts, such as 2-4-fold rises in concentrations of hexokinase, peptidyl proline hydroxylase and thymidine kinase, and b70% reductions in soluble glutamate dehydrogenase and cold-stable pyrroline-5-carboxylate reductase. 8 Overall, liver enzymes showed a striking pattern of dedifferentiation resembling enzymic changes observed within malignant tumours. A similar dedifferentiation of liver enzyme patterns was observed in various experimental cancer models, including renal, submaxillary and mammary cancer.…”
Section: Introductionmentioning
confidence: 97%
“…However, overexpression of the mRNA for P5CR was reported by DNA microarray analysis in carcinoma, [12][13][14] and the raised activity of P5CR changes as a marker of pulmonary tumors and adult neoplastic colon. 15,16 The decreased P5CR activity may be associated with retinal degeneration in mice, 17 and could be used to distinguish clearly between patients with and without non-hepatic cancer. 6 The expression of P5CR in LoVo cells can be inhibited by adriamycin.…”
Section: Introductionmentioning
confidence: 99%
“…PYCR1 exhibits the capability to protect cells from mitochondrial fragmentation induced by oxidative stress [ 16 ]. Furthermore, investigations have revealed that PYCR1 overexpression and increased activity have been observed in various carcinoma types, encompassing lung, prostate, colon, liver, and breast cancers [ [17] , [18] , [19] , [20] , [21] ]. PI3K/AKT pathway plays an important role in inducing cell malignant transformation, tumor angiogenesis and apoptosis [ 22 ].…”
Section: Introductionmentioning
confidence: 99%